2018
DOI: 10.1176/appi.ps.201700194
|View full text |Cite
|
Sign up to set email alerts
|

A Change in Perspective: From Dual Diagnosis to Multimorbidity

Abstract: Real-world psychiatric care is more accurately approached from the multimorbidity perspective than from the perspective of principal, dual, or comorbid diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…However, a recent study reported that nine out of 10 of the most common patient-reported reasons for primary care visits were nonpsychiatric [ 110 ], indicating that this outcome was likely to be mainly nonpsychiatric. It is very common for patients to have other psychiatric illnesses alongside SMI [ 111 ]. Unfortunately, because of the nature of the studies included, it was not within the scope of the current review to consider the impact of the overlap between SMI and other psychiatric conditions on nonpsychiatric health service utilisation.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study reported that nine out of 10 of the most common patient-reported reasons for primary care visits were nonpsychiatric [ 110 ], indicating that this outcome was likely to be mainly nonpsychiatric. It is very common for patients to have other psychiatric illnesses alongside SMI [ 111 ]. Unfortunately, because of the nature of the studies included, it was not within the scope of the current review to consider the impact of the overlap between SMI and other psychiatric conditions on nonpsychiatric health service utilisation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the findings of a recent study conducted in the Veterans Health Administration (16), ECT patients (when compared with non-ECT patients) had substantially higher rates of personality disorders (RR=7.37) and alcohol dependence (RR=2.12); much higher rates of prescription fills for antipsychotics (RR=3.58), mood stabilizers and anticonvulsants (RR=2.01), and lithium (RR=6.03); and higher prescription fill rates of all psychotropics (Cohen’s d=.77). ECT thus appears to be used among patients with multimorbidity who have more complicated psychiatric disorders (23), perhaps as a treatment of last resort when clinicians judge other treatment possibilities to have failed.…”
Section: Discussionmentioning
confidence: 99%
“…9À11 A variety of clinicians and researchers have questioned the validity of the categorical approach to these diseases, as psychotic symptoms can be present in both diseases, suggesting that they are less distinct than the DSM and ICD indicate. 9,12 In fact, several recent studies have shown that the majority of real-world patients have multiple psychiatric disorders, 13,14 and rates of mental health multimorbidity tend to be higher in patients with schizophrenia and BD compared with other psychiatric patients. 15,16 Psychiatric multimorbidity, and its associated clinical complexity, is increasingly recognized as ubiquitous by mental health professionals and according to research.…”
Section: Introductionmentioning
confidence: 99%